FACTORS INFLUENCING STUDENT MENTAL HEALTH AT ARJUNA HEALTH COLLEGE, LAGUBOTI DISTRICT, TOBA REGENCY - Luqitawati Manurung; Ismail Efendy; Nuraini Nuraini (Universitas Teuku Umar, 2025)
The 2023 Indonesian Health Survey (SKI) data shows a depression prevalence of 1.4% nationally, with the highest rate in the 15-24 age group. However, many are still reluctant to seek professional help due to stigma. This study aims to analyze the factors that affect the mental health of students at STIKes Arjuna.The research is a quantitative study with a descriptive correlational survey method to determine the relationship between emotional intelligence, psychological, and social factors with the mental health conditions of students (depression, anxiety, and stress). Based on 158 student sample from STIKes Arjuna using a structured questionnaire. The variables studied included emotional intelligence factors, psychological factors, social factors, and mental health.The results showed no significant relationship between emotional intelligence and mental health (depression, anxiety, and stress), with a sig p=0.799, sig p=0.253, and sig p=0.065, respectively. Psychological factors have a significant influence on mental health,namely depression and stress, with a sig p-value= 0.025 and sig p=0.02. Psychological factors did not have a significant effect on mental health, namely anxiety, as evidenced by a p-value of 0.021. In the social factors, the research results show that is has an influence significant to mental health, namely depression, anxiety, and stress,as indicated by the values sig-p= 0.011, sig- p=0.010, and sig-p=0.000.It is hoped that mental health education and related facilities will be integrated into the curriculum, and students will be open and honest about their conditions and be aware of seeking health services. Further research is suggested to explore other factors influencing mental health and mediating factors between variables